2019
DOI: 10.1007/s40520-019-01171-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of poor sleep quality among Chinese older adults living in a rural area: a population-based study

Abstract: Objective To investigate the prevalence and associated factors of poor sleep quality among community-dwelling elderly population in a rural area of Northern China. Methods We conducted a cross-sectional survey in August-December 2014 and recruited 2195 participants who were aged 65 years or older and living in Yanlou Town of Yanggu County in western Shandong Province, China. Data on demographics, health-related behaviors, and clinical conditions were collected through structured interviews. The Pittsburgh Slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
82
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 51 publications
14
82
1
3
Order By: Relevance
“…Substantial concrete evidence indicated that there was a significant negative effect on the individual's sleep health when people engaged in health-related risk behavior(s) [19,20,32,33]. This study concluded that with an increase in health-related risk behaviors, the negative effects on sleep health could be further increased, at least for both the increased prevalence of sleep problems and the deterioration of sleep quality.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Substantial concrete evidence indicated that there was a significant negative effect on the individual's sleep health when people engaged in health-related risk behavior(s) [19,20,32,33]. This study concluded that with an increase in health-related risk behaviors, the negative effects on sleep health could be further increased, at least for both the increased prevalence of sleep problems and the deterioration of sleep quality.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies from developed countries or regions have confirmed the link between specific behaviors and sleep health. Health-related behavioral risk factors, including tobacco use, alcohol drinking, unhealthy dietary behaviors, as well as insufficient time for leisure activities and physical inactivity, have been shown to be associated with sleep health [17,19,20,32,33]. The results of these studies provide the theoretical basis for developing interventions that specifically target a particular health-related risk behavior.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations